2018
DOI: 10.1002/slct.201702650
|View full text |Cite
|
Sign up to set email alerts
|

High Efficient Cu2O/TiO2 Nanocomposite Photocatalyst to Degrade Organic Polluant under Visible Light Irradiation

Abstract: The enhanced photocatalytic properties of Cu 2 O/TiO 2 nanocomposites resulting from the synthesis of uniform p-type Cu 2 O and n-type TiO 2 via wet chemical method were studied. The nanocomposite also had been well characterized and tested for its photocatalytic activity. These results indicate that the photocatalytic performance of the composites is clearly improved. The degradation rate of methylene blue solution (10 mg/L) increased to 93.67% in 45 minutes. The p-n heterojunction theory was used to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This morphological approach is successful to enhance the photocatalytic activity under UV illumination [9][10][11][12]. Other options to limit recombination include the addition of other semiconductors to obtain heterojunctions [13][14][15][16] or the doping with cations [17][18][19][20]. Among the various candidates for TiO2 doping, copper is a promising choice.…”
Section: Introductionmentioning
confidence: 99%
“…This morphological approach is successful to enhance the photocatalytic activity under UV illumination [9][10][11][12]. Other options to limit recombination include the addition of other semiconductors to obtain heterojunctions [13][14][15][16] or the doping with cations [17][18][19][20]. Among the various candidates for TiO2 doping, copper is a promising choice.…”
Section: Introductionmentioning
confidence: 99%
“…These organic pollutants need to be degraded to lower their impact on the environment because they tend to be toxic. [1][2][3] Primarily, water pollution demands focus urgently. Semiconductor photocatalysis can be an excellent solution to the severe problem of pollution.…”
Section: Introductionmentioning
confidence: 99%
“…From the studies reported, n-type TiO 2 coupling with p-type Cu 2 O exhibits good prospects for photocatalytic applications under visible light. For example, it was used in different applications such as the removal of organic and inorganic pollutants [20,[25][26][27][28], CO 2 reduction [29,30], H 2 evolution [14,[31][32][33], polyester textiles [34], as well as for antibacterial activity [35,36].…”
Section: Introductionmentioning
confidence: 99%